2022
DOI: 10.1111/aor.14471
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the decarboxylation index to predict CO2 removal and minute ventilation reduction under extracorporeal respiratory support

Abstract: Background:The aim of this study was to assess the interdependence of extracorporeal blood flow (Qec) and gas flow (GF) in predicting CO 2 removal and reduction of minute mechanical ventilation under extracorporeal respiratory support.Methods: All patients who benefited from V-V ECMO and high-flow ECCO 2 R in our intensive care unit over a period of 18 months were included. CO 2 removal was calculated from inlet/outlet blood port gases during the first 7 days of oxygenator use. The relationship between the Qec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Extracorporeal respiratory support via V-V ECMO or ECCO 2 R is used increasingly in critically ill setting. [6][7][8][9]28,29 Determinants of extracorporeal decarboxylation are numerous: oxygenator surface, sweep gas flow, pre-oxygenator PCO 2 , but also Q EC as demonstrated recently by Laumon et al [10][11][12][13][14] In clinical practice, consideration of all these parameters helps to predict CO 2 elimination under extracorporeal respiratory support, which is based on changes of CO 2 content into extracorporeal circulation. However, the equations determining CO 2 content in blood are old and complex, and were established in a healthy population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extracorporeal respiratory support via V-V ECMO or ECCO 2 R is used increasingly in critically ill setting. [6][7][8][9]28,29 Determinants of extracorporeal decarboxylation are numerous: oxygenator surface, sweep gas flow, pre-oxygenator PCO 2 , but also Q EC as demonstrated recently by Laumon et al [10][11][12][13][14] In clinical practice, consideration of all these parameters helps to predict CO 2 elimination under extracorporeal respiratory support, which is based on changes of CO 2 content into extracorporeal circulation. However, the equations determining CO 2 content in blood are old and complex, and were established in a healthy population.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we demonstrated that the product sweep gas flow × Q EC reliably predicts CO 2 elimination; this is the prescribed decarboxylation index. 14 However, its predictive value is robust only in the absence of oxygenator alterations or other confounding factors. In contrast, current study has assessed the delivered decarboxylation index; the ∆ EC PCO 2 × Q EC product was found to be linearly associated with the amount of CO 2 that was removed by extracorporeal support (model 5); each additional unit of the ∆ EC PCO 2 × Q EC product predicted an increase in CO 2 elimination of 5.2 ml STPD/min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations